"Context, Please?" The Effects of Appearance- and Health-Frames and Media Context on Body-Related Outcomes - Alice Binder; Selina Noetzel; Ines Spielvogel; Jörg Matthes (Frontiers Media S.A., 2021)
Promoting health-related behaviors such as healthy eating or doing sports are important to counteract the problem of obesity, which is on the rise. In this regard, initial studies suggest that appearance compared to health framing can lead to negative body-related outcomes in young women. This study aimed to extend these findings by investigating the role of the context. Furthermore, as previous studies focused on young women only, we considered a more diverse sample. This seems especially important as health campaigns focusing on healthy eating and sports should appeal to a more diverse population. This experimental study (N = 286) follows a 2 (appearance frame vs. health frame) × 2 (social media vs. magazine website) between-subjects design. Results revealed that exposure to appearance-focused framing led to a lower positive mood compared with exposure to health-focused framing. These effects were most prevalent in overweight and obese participants. Moreover, participants in the social media condition showed lower body satisfaction and lower positive mood compared with participants in the magazine website condition independent of the frame. No other interaction effects occured. Overall, health promoters should focus their campaigns on the health aspects of health-related behaviors and should consider promotion on social media platforms. Also, they should keep in mind that not only the framing, but also the context, might have effects on body-related outcomes.